2020
DOI: 10.1007/s00406-020-01168-1
|View full text |Cite|
|
Sign up to set email alerts
|

Cortical activation abnormalities in bipolar and schizophrenia patients in a combined oddball–incongruence paradigm

Abstract: Patients with bipolar disorder and schizophrenia often suffer from severe cognitive impairment even during times of remission. This study investigated the pathomechanisms underlying their deficits in cognitive control. A combined oddball–incongruence fMRI task was applied to examine similarities and differences of neural activation patterns between patients and healthy controls. Bipolar and schizophrenia patients demonstrated hyperactivations in the intraparietal cortex during the oddball condition. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…There is significant evidence regarding the functional connectivity of neural networks connecting brain regions in patients with schizophrenia. Research conducted with transcranial magnetic stimulation technology has demonstrated that there is a malfunction of cortical networks [ 131 , 132 ] thus leading to severe cognitive dysfunction. The occurrence of these abnormalities is determined, most of the time, by the expression of genetic polymorphisms or mutations [ 133 ].…”
Section: Anatomical Changes and Their Impactmentioning
confidence: 99%
“…There is significant evidence regarding the functional connectivity of neural networks connecting brain regions in patients with schizophrenia. Research conducted with transcranial magnetic stimulation technology has demonstrated that there is a malfunction of cortical networks [ 131 , 132 ] thus leading to severe cognitive dysfunction. The occurrence of these abnormalities is determined, most of the time, by the expression of genetic polymorphisms or mutations [ 133 ].…”
Section: Anatomical Changes and Their Impactmentioning
confidence: 99%